Terror in gunsight [large type] - Paine, Lauran (Circle V western., 2018)
"U.S. Deputy Marshal Ben Knight takes off his badge and rides into Gunsight seeking vengeance for his kid brother's hanging. But the town marshal was killed during the lynching and the townspeople want Ben to take his place. Ben must choose between his trail of vengeance or protecting the town against the Diamond H Ranch"--